1999
DOI: 10.1086/300897
|View full text |Cite
|
Sign up to set email alerts
|

The Fall and Rise of V854 Centauri: Long-Term Ultraviolet Spectroscopy of a Highly Active R Coronae Borealis Star

Abstract: We examine long-term low-dispersion International Ultraviolet Explorer SWP and LWP spectroscopy of the R Coronae Borealis (RCB) star V854 Cen, obtained across the deep (*V [ 6 mag) 1991, 1992È 1993, and 1994 declines. We also report the optical light curve for the star in the interval 1987È1998, including multicolor photometry obtained during 1989È1998. The light curve includes at least eight major declines where the amplitude exceeds 5 mag, many of which appear to be multiple decline events. Analysis of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 27 publications
(72 reference statements)
3
23
1
Order By: Relevance
“…We found that all of the major declines, and most of the minor ones (excluding those for which the AAVSO sampling was poor), could be tied to the respective pulsation periods. Our results, therefore, substantiate the pulsation-decline connections claimed for RY Sgr and V854 Cen by Pugach (1977) and Lawson et al (1992Lawson et al ( , 1999, respectively, and significantly extend the relationship through the introduction of three other RCB stars (UW Cen, R CrB and S Aps) that show the same type of behaviour. This work firmly demonstrates the link between radial pulsations and the ejection of material in the RCB stars.…”
Section: Starsupporting
confidence: 92%
See 4 more Smart Citations
“…We found that all of the major declines, and most of the minor ones (excluding those for which the AAVSO sampling was poor), could be tied to the respective pulsation periods. Our results, therefore, substantiate the pulsation-decline connections claimed for RY Sgr and V854 Cen by Pugach (1977) and Lawson et al (1992Lawson et al ( , 1999, respectively, and significantly extend the relationship through the introduction of three other RCB stars (UW Cen, R CrB and S Aps) that show the same type of behaviour. This work firmly demonstrates the link between radial pulsations and the ejection of material in the RCB stars.…”
Section: Starsupporting
confidence: 92%
“…RCB stars with similar physical and pulsational properties include RZ Nor, RS Tel, RT Nor, SU Tau, GU Sgr and XX Cam, but unfortunately these objects are not as well observed by the Decline onsets used to determine the decline ephemeris are marked with crosses. Grey crosses identify decline onsets from Lawson et al (1992Lawson et al ( , 1999, whereas black crosses are decline onsets identified in this paper.…”
Section: A Av S O V I S Ua L O B S E Rvat I O N Smentioning
confidence: 64%
See 3 more Smart Citations